The state and prospects of preservation of some rare and relic species Lycopodiophyta at southern megaslope of the Ukrainian Carpathians (Transcarpathia) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The results of researches are represented for three species of divisio Lycopodiophyta (Diphasiastrum issleri (Rouy) Holub, Lycopodiella inundata (L.) Holub), Selaginella helvetica (L.) Spring, which are rare in Ukrainian Carpathians. Detailed description is provided for the habitats and plant communities, where these species occur; the number of individuals in the populations is detected. Their sozological status is defined with the forecast of populations’ development for the nearest years.
Keywords: Ukrainian Carpathians, Transcarpathia, Diphasiastrum issleri, Lycopodiella inundata, Selaginella helvetica, habitat, areal dynamics, community characteristic, sozological state.